MEANINGS AND IDENTITY SYMBOLS BEHIND DEATH: LINGUISTIC LANDSCAPE AREAS OF JAPANESE CEMETERY IN SUMATERA UTARA AND ACEH - Adriana Hasibuan; Rani Arfianty (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2025)
During the Japanese occupation of North Sumatra and Aceh, many Japanese soldiers and civilians died. Since Japanese people living in North Sumatra and Aceh did not have kamei (family name) and kamon (family symbol), they were buried in public cemeteries, such as Bukit Barisan Heroes Cemetery in Medan (TMPBB), Kerkhof Cemetery in Banda Aceh, and Japanese cemetery in Delitua, Deli Serdang district. Data were collected directly in the three cemeteries on the inscription texts of 65 headstones and texts on 14 signboards scattered in the cemetery with documentation techniques (photographs). The data totalled 367 texts, classified based on Chenoz & Gorter's (2007) Top-Down and Bottom-Up construction patterns to see the form and pattern of language use. Data analysis used Lechte's semiotic theory in Sobur (2017), text semiotics theory (Piliang: 2004), linguistic landscape theory (Landry and Bourhis: 1997) and language contestation: dominant and marginal languages were analysed with Bakhtin's theory (1981). The texts in the three burial areas are monolingual, bilingual and multilingual, namely Indonesian, Arabic, Japanese, English, Dutch and Acehnese. This indicates that Japanese burial areas are synonymous with symbols of language competence. At the TMPBB in Medan, Indonesian-Arabic is dominant, because the Japanese are Muslims and have become Indonesian citizens. Kerkhof Cemetery in Banda Aceh has four forms of language, namely Acehnese, Indonesian, Dutch and Japanese, and is dominated by Dutch graves. In the Japanese burial area in Delitua there are two forms of language, namely Japanese-Indonesian, and text written in Japanese characters. The use of language in these three Japanese burial areas is identical to the characteristics of religion, culture, social system, history, and locality. The texts also provide information messages in the form of identity, social status, prohibitions/commands, advice and sacredness. The symbols embodied in the linguistic landscape of Japanese funerals in Sumatra and Aceh are multilingual: Acehnese-Indonesian as a locality, Arabic as a symbol of Islamic religious entities, Japanese and Dutch as symbols of history and a dark colonial past, and English as a symbol of the religious tourism industry.